Pengaruh Pendidikan Etika Bisnis, Religiusitas, Gender, dan Performa Akademik terhadap Persepsi Etis Mahasiswa Akuntansi - Hendy Agustinus (International Journal of Social Science and Business, 2020)
This study aims to examine whether there is influence of business ethics education, gender, religiosity, and Academic Performance of the Ethical Perceptions of accounting students who have worked in the city of Semarang. Independent variables in this research are business ethics education, gender, religiosity, and Academic Performance. The sample was taken by using purposive technique and obtained 90 respondents. The result of different test of independent sampl t-test shows that there is a significant difference between students who have not and have taken etbis courses on their ethical perception in making decision. There is a significant difference between students who have a GPA above or equal to 3.3 with students who have GPA below 3.3 on their ethical perceptions of decision making There is no significant difference between male and female students on their ethical perceptions in making decisions. There is a significant difference between students who have high degree of religiosity with students who have a low degree of religiosity their ethical perceptions in making decisions. Key words: Ethical Perception, Academic Performance, Religiusity, Gender, Business Ethics Education.